Temperamental predictors of developmental trajectories of inattention and hyperactivity–impulsivity problems in schoolchildren - Soo Jin Lee; Soo-Hyun Park; Ansuk Jeong; Han Chae; Kyungja Oh (Integrative Medicine Research)
Background: The current study aimed to examine the temperamental predictors of developmental trajectory subgroups of children's inattention and hyperactivity–impulsivity problems through a short-term longitudinal study. Methods: Children (n = 1344) were divided into younger (age 6–8 years) and older (age 9–11 years) groups in order to observe changes in inattention and hyperactivity–impulsivity problems. Inattention and hyperactivity–impulsivity problems were measured three times at 5-month intervals and Cloninger's four temperaments (novelty seeking, harm avoidance, reward dependence, and persistence) were examined on the first occasion only. A cohort sequential design and growth mixture model were used for investigating trajectory subgroups and multiple logistic regression analysis to examine the temperamental predictors. Results: Developmental trajectories of inattention and hyperactivity–impulsivity showed different subgroupings depending on the age group of children. Temperament (high score on novelty seeking and low score on persistence as well as high score on reward dependence) and gender predicted the likelihood of belonging to high-risk versus low-risk subgroups. Conclusion: Suggestions taking into account the predictors of developmental trajectories in inattention and hyperactivity–impulsivity problems for future research are discussed along with the limitations of the current study.